Controlling the growth temperature gradient and interface shape for traveling heater method growth of CdTe single crystals - Suh, Youngjoon; Kim, Jin-Sang; Suh, Sang-Hee (HARD X-RAY, GAMMA-RAY, AND NEUTRON DETECTOR PHYSICS XVIII, 2016)
The temperature gradient at the growth interface is as important as the growth temperature and the growth rate for growing CdTe single crystals by the Traveling Heater Method (THM). This article presents the results of an experimental study of the influence of the growth temperature gradient on THM growth of CdTe single crystals. CdTe crystals were grown at about 900 degrees C with the growth rate of 10 mm/day and the rotation rate of 3 rpm. With the growth temperature gradient of about 30 degrees C/cm even a single-grain structure became a multi-grain structure in the final stage of growth. On the other hand, with the growth temperature gradient of about 50 degrees C/cm, even if the crystal started with multi-grains, it became a single crystal eventually. The constitutional supercooling criterion was used to interpret these results.